Study of the variation of contact state near the contact boundary in a dovetail attachment under different loads. (November 2019) - Wei, Da-Sheng; Ma, Meng-Di; Zhang, Hui; Hu, Chen; Wang, Yan-Rong
Abstract: It is very important to characterize the variation of cyclic parameters near the contact edge in dovetail attachments for understanding the fretting fatigue mechanism. In this paper, the variation of contact state in a dovetail attachment was studied by using the finite element method (FEM), which is affected by two key factors i.e. the relative slip and the mutual compaction. When the flank angle and the coefficient of friction are constant, the influence of compaction seems much more obvious under centrifugal loads, and the edge of contact zone would move up along the contact surface. However, the influence of relative slip becomes much more obvious under tensile loads, and the edge of contact zone would move down. The movement of contact edge shows a similar trend under cyclic loads, which may result in the movement of position where the high stress gradient locates, and the numerical results show that the negative stress ratio would occur near the contact edge. Highlights: The variation of the contact state and the reason under different types of loads are studied. The mechanical parameters under different types of loads near the contact edge are obtained. The reason of the variation of the contact state can be explained by relative slip and compaction.